Factors associated with protean career - Fung, Ying Ying. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The widespread oforganizational transformation and business world uncertainty in recent decades had led to demise of traditional careers and the emergence of protean career. This study aims to identify the factors that are associated with protean career by conducting a survey research in one ofprivate organization in Kuching. A total of 70 questionnaires were returned out of 110 questionnaires distributed through convenience sampling and only 55 questionnaires were usable for real study. Data obtained were analyzed using Independent Sample t-Test and Pearson Correlation. The statistical analysis showed that gender had no significant difference in protean career. In the meantime, the subjective career success, organizational learning climate, and calling orientation had a significant relationship with protean career. Hence, subjective career success, organizational learning climate, and calling orientation were crucial for protean career. Accordingly, the organization should continue empower their employees to self manage their career while provide them with continuous learning opportunities. In between, the HR practitioners should provide career counseling and construct an effective environment for organizational learning in order to enhance the employees ' protean career management.